Study On pH Reduction Between Ceramic Flat And Sand Filtration Method In Kangkar Senangar, Parit Sulong, Johor - Muhammad Eizaz Dhiya Bin Ishak; Tajul Baharuddin, Mohamad Faizal (Progress in Engineering Application and Technology, 2023)
Sand filtration method are used to filter groundwater water from tube wells in the Johor villages of Kampung Lama Orang Asli Leboh, Kangkar Senangar, Parit Sulong, Batu Pahat. For more than 50 years, residents in this town have struggled to obtain safe drinking water. Despite having an established sand filtering system, the problem of clean water sources remains unsolved due to a lack of an efficient maintenance system. The ceramic flat membrane was brought in to enhance the the efficiency of pH reduction of the groundwater. The ceramic flat was provided with water from the tube well. Before and after attaching it to the tubewell, the pHvalue was determined. The pH of the filtered water was measured using a WTW 251210 pHotoFlex® Turb/SET Portable LED filter photometer accordance to APHA 2005. Both result coming from the filtration method were at the same with no significant increase or decreasse. This happen may due to corrosion reactions that occur somewhere along the extended down-hole equipment, while reduction reactions occur where the current direction is inward. If this occurs in the sampled borehole section, the pH of the samples will be high. Moreover, contamination also may came from the pump equipment, such as deterioration of plastic materials and oxidation processes. This is the first study that determine the pH reduction of groundwater using Ceramic Flat Membrane in Kampung Kangkar Senangar, Parit Sulong, Batu Pahat.